Patients’ Knowledge about Safe Measures Post Implantable Cardioverter Defibrillator - Mohammed Kadhum Sadaq; Abed Ali Hattab, Wafaa (Iraqi Journal of Pharmaceutical Sciences, 2025)
Patients who have implantable cardioverter defibrillators (ICD) are challenged with multiple physical, psychological, and social complications. It is important to understand ICD patients’ knowledge about safe measures post-implementation. The study aims to assess patient’s knowledge of the safe measures after implantable cardioverter defibrillator. A descriptive-analytical study was carried out from October 19th, 2022 to January 16th, 2024 to determine the patient’s knowledge about safe measures after ICD. Non-probability (purposive) sample of 70 Patients with an ICD during routine checking and programming the device in outpatient at Ibn – Al-Bitar specialized center in Baghdad city. The study instrument was composed of three parts, socio-demographic characteristics, medical information, and patient’s knowledge of the safe measures after ICD implantation. Data were analyzed through the application of descriptive and inferential data analysis approaches by using SPSS version 26. The results of the study show majority of the sample was male, married, and aged (42- less than 54) years and the maximum age of patients who attended to study was 76 years, they did complete the primary educational level, and a high percent were unemployed. also, most of the sample was median income, and their duration of implantation is 5 years & above. The maximum duration of implantation of patients who attend the cardiac center is 14 years. The majority of patients were not smokers. Patients’ knowledge of safe measures post-ICD was fair to the level regarding safe activity and electrical devices. and the poor level of magnetic devices and medical devices. There is a significant association among the patients’ knowledge with sex and education level variables at P ≤ 0.05. Conclusion: The knowledge of patients regarding safe measures post-ICD was poor level as general. Post-intervention education should be especially important to patients to avoid unnecessary limitations.